Manual Version of 3D Printing - Lytvynenko, Yu.M.; Ostapenko, S.O.; Rogozinsky, A.А.; Solonin, Yu.M. (Наука та інновації, 2019)
Introduction. The program of colonization of the Moon and Mars is gradually approaching the practical phase. Researchers are actively discussing various aspects of the presence of people on the surface of the planets. Problem Statement. The number one problem is housing construction: materials and construction technologies. The use of regolith — the lunar or the Martian soil — is supposed to be used as a building material. The construction technology involves the placement of astronauts heating furnace on the lunar surface for sintering bricks, followed by laying them in building structures. The bricks will print on a 3D printer. This idea will require the development and delivery of a 3D printer to the lunar base. Purpose. It is interesting to check the possibilities of simple and cheap options for creating building elements in the conditions of the lunar surface in the absence of a 3D printer and complex heating devices. The purpose of the research is to make a simple product by an additive method, modeling the process of 3D printing without expensive and complicated instruments and devices. Materials and Methods. The manual version of 3D printing using concentrated solar energy from minimally processed local regolith is a simple, economical method of making building components on the surface of the Moon or Mars. The materials used were sand and basalt of terrestrial origin. All necessary operational work for modeling the 3D printing process was done manually. Various devices were used to concentrate the sun's rays on the basis of paraboloid concentrators to create a thermal source of the printer. Results. Simple products from basalt powders and mixtures of basalt with sand were obtained by an additive method without the use of complex expensive equipment. A primitive installation for a 3D process and a heating device from paraboloid concentrators can be easily assembled from structural elements brought from Earth. Conclusions. Manual 3D printing of a minimally processed local regolith using concentrated solar energy is a simple, economical method of making building components on the surface of the Moon or Mars. Вступ. Програма колонізації Місяця й Марса поступово наближається до практичної фази. Вчені активно обговорюють різні аспекти перебування людей на поверхні цих планет. Проблематика. Першочерговою проблемою в цьому процесі є будівництво житла, зокрема питання матеріалів та технології будівництва. Як будівельний матеріал передбачено використання реголіту — місячного або марсіанського ґрунту. Технологія будівництва передбачає розміщення космонавтами нагрівальної печі на місячній поверхні для спікання цегли з подальшим укладанням її в будівельні конструкції. Цеглини будуть друкувати на 3D-принтері. Ця ідея потребує розробки та доставки 3D-принтера на місячну базу. Мета. Перевірка можливості реалізації простих і низьковартісних варіантів створення будівельних елементів в умовах місячної поверхні за відсутності 3D-принтера та складних нагрівальних приладів. Розробка адитивним методом простого виробу, модeлюючи процес 3D-друкування без використання високовартісних і складних приладів та пристроїв. Матеріали й методи. Ручний варіант 3D-друкування з використанням концентрованої сонячної енергії з мінімально обробленого місцевого реголіту є простим економічним способом виготовлення будівельних компонентів на поверхні Місяця або Марса. Як матеріали використано пісок і базальт земного походження. Всі необхідні оперативні роботи для моделювання 3D-процесу друку було виконано вручну. Для створення теплового джерела принтера використано різні пристрої для концентрування сонячних променів на базі параболоїдних концентраторів. Результати. Виготовлено прості вироби з порошків базальту та сумішей базальту з піском адитивним методом без використання складного високовартісного устаткування. Примітивна установка для 3D-процесу та нагрівальний пристрій з параболоїдних концентраторів можуть бути легко зібрані з елементів конструкцій, транспортованих із Землі. Висновки. Ручне 3D-друкування мінімально обробленого локального реголіту з використанням концентрованої сонячної енергії є простим економічним способом виготовлення будівельних компонентів на поверхні Місяця або Марса. Введение. Программа колонизации Луны и Марса постепенно приближается к практической фазе. Ученые активно обсуждают различные аспекты пребывания людей на поверхности этих планет. Проблематика. Первоочередной проблемой в этом процессе является строительство жилья, в частности, материалы и технологии строительства. В качестве строительного материала предполагается использование реголита — лунного или марсианского грунта. Технология строительства предполагает размещение космонавтами нагревательной печи на лунной поверхности для спекания кирпичей с последующей укладкой их в строительные конструкции. Кирпичи будут печатать на 3D-принтере. Эта идея потребует разработки и доставки 3D-принтера на лунную базу. Цель. Проверка возможности простых и недорогих вариантов создания строительных элементов в условиях лунной поверхности при отсутствии 3D-принтера и сложных нагревательных приборов. Разработка аддитивным методом простого изделия, модeлируя процесс 3D-печати без использования дорогих и сложных приборов и устройств. Материалы и методы. Ручной вариант 3D-печати с использованием концентрированной солнечной энергии из минимально обработанного местного реголита представляет простой экономичный способ изготовления строительных компонентов на поверхности Луны или Марса. В качестве материалов использовались песок и базальт земного происхождения. Все необходимые оперативные работы для моделирования 3D-процесса печати были выполнены вручную. Для создания теплового источника принтера использованы различные устройства для концентрирования солнечных лучей на базе параболоидных концентраторов. Результаты. Получены простые изделия из порошков базальта и смесей базальта с песком аддитивным методом без использования сложного дорогостоящего оборудования. Примитивная установка для 3D-процесса и нагревательное устройство из параболоидных концентраторов могут быть легко собраны из элементов конструкций, привезенных с Земли. Выводы. Ручная 3D-печать минимально обработанного локального реголита с использованием концентрированной солнечной энергии представляет собой простой экономичный способ изготовления строительных компонентов на поверхности Луны или Марса.